Budget impact of niraparib as maintenance treatment in recurrent ovarian cancer following platinum-based chemotherapy. (2nd April 2019) - Neeser, Kurt; O'Neil, William M; Stern, Lee; Harrow, Brooke; Travers, Karin
Aim: To estimate financial implications of adopting niraparib as maintenance treatment in recurrent ovarian cancer.Materials & methods: A model was developed to estimate the budget impact of treating patients with niraparib compared with alternative maintenance treatment options (olaparib, rucaparib, bevacizumab or 'watch and wait') over 3 years.Results: For a hypothetical plan with 1 million lives representative of US/Medicare-only populations, projected cost savings with niraparib were US$78, 721/$293, 723, $276, 671/$1, 009, 729 and $353, 585/$1, 289, 712 at years 1, 2 and 3, respectively. Sensitivity analyses showed prices of niraparib, rucaparib and olaparib to have the most significant impact on the budget.Conclusion: Factoring in all treatment-related costs, the use of niraparib could result in significant cost savings compared with other maintenance treatment options.